2019
DOI: 10.1159/000502790
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Cytology of the Testes for the Classification of Azoospermia and Its Value in the Assessment of Male Infertility

Abstract: Background: Infertility is an ever-increasing problem in today's world. It can be due to male or female causes. Azoospermia seen in 5-10% of infertile men is due to obstructive or non-obstructive causes. Traditionally, testicular biopsy is the gold standard for evaluation. Fine-needle aspiration (FNA), however, is minimally invasive, provides qualitative and quantitative information about spermatogenesis, and can aid in assisted reproductive techniques making it a novel technique for the evaluation of male inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The patient's age range was 22 to 47 years, with a mean of 34.6 years of age, similar to reported by others. 8,9,10,11 Among the service seekers, 57.22% were in the age group of 31-40 years and 28.86% in 21-30 years. This finding was near to the report of Rahaman et al in 2016 as they found 63% of their respondent, male infertile, was in the age group of 31-40 years [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The patient's age range was 22 to 47 years, with a mean of 34.6 years of age, similar to reported by others. 8,9,10,11 Among the service seekers, 57.22% were in the age group of 31-40 years and 28.86% in 21-30 years. This finding was near to the report of Rahaman et al in 2016 as they found 63% of their respondent, male infertile, was in the age group of 31-40 years [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on pathological features, azoospermia can be classified into obstructive azoospermia (OA) and non-obstructive azoospermia (NOA). With the development of assisted reproductive technology, techniques such as intracytoplasmic sperm injection have made it possible for most patients with OA to conceive their own offspring [ 3 , 4 ]. However, it is a challenge to retrieve sperms from patients with NOA, even by microsurgical testicular sperm extraction (microTESE) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of assisted reproductive technology (ART), such as intracytoplasmic sperm injection (ICSI), has allowed most patients with OA to conceive their own offspring [3,4]. However, sperm retrieval in NOA patients has always been di cult even by microsurgical testicular sperm extraction (microTESE) [5,6].…”
Section: Introductionmentioning
confidence: 99%